Improvisation Scat Singing in Mbiring Manggis Song: An Interpretive Approach to Karo Traditional Music - Naima Serenia Girsang (TALENTA Publisher, 2025)
This research aims to analyze the relationship between scat singing vocal improvisation techniques and the development of vocal interpretation in a traditional Batak Karo song entitled Mbiring manggis . The scat singing technique, which comes from the jazz vocal tradition, is rarely used in the context of folk songs. Therefore, its application in the song Mbiring mangosteen offers a new approach in enriching the traditional vocal arrangement style. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, documentation, and musical exploration conducted in the process of rehearsal and song recording. The results showed that the application of scat singing can improve the singer's musical expression through rhythmic flexibility, improvisational syllable selection, and strengthening the meaning of emotions in the lyrics. The vocal interpretations not only retain the original characteristics of Karo songs, but also create new musical colors that can reach modern audiences. This research recommends further exploration of the collaboration of jazz vocal techniques and traditional music as a strategy for preservation and innovation.